2007
DOI: 10.1007/s00464-006-9038-2
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical master–slave manipulator: an instrument improving the performance in standardized tasks for endoscopic surgery

Abstract: The tasks clearly demonstrated the efficacy of the mechanical manipulator, although some technical flaws emerged during the experiments. Considering the fact that a first prototype of the mechanical manipulator was tested, modifications are to be expected in a next model. These experiments show the potential of the mechanical manipulator, and it is expected to be a competitive and economical instrument for endoscopic surgery in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An additional number of DOFs with respect to conventional endoscopic instruments was shown to be favourable. Diks et al (17) reported that novices showed less actions and failures with the MIM than with COV during laboratory experiments. .…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…An additional number of DOFs with respect to conventional endoscopic instruments was shown to be favourable. Diks et al (17) reported that novices showed less actions and failures with the MIM than with COV during laboratory experiments. .…”
Section: Methodsmentioning
confidence: 98%
“…During previous knot-tying experiments, the suture wire was often caught inside the wrist mechanism, while the needle tip design embodied some rugged parts and the joints were unshielded (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We know of only one nonrobotic articulated device for laparoscopic surgery that is not handheld: Jaspers and Diks et al developed a mechanical manipulator that utilizes a pantograph mechanism to control two surgical bed-mounted endoscopic arms, each with seven degrees of freedom [20,21]. While this device provides many of the advantages of the da Vinci robot in a purely mechanical form, reconfigurability is limited by the need to mount it to the surgical bed.…”
Section: Introductionmentioning
confidence: 99%